Antiosteoporosis effect of tanshinol in osteoporosis animal models: A systematic review and meta-analysis - Wang, Shen; Yuan, Yifeng; Lin, Qian; Zhou, Hang; Tang, Binbin; Liu, Yang; Huang, Hai; Liang, Bocheng; Mao, Yingdelong; Liu, Kang; Shi, Xiaolin (Frontiers in Pharmacology, 2022)
Background: Osteoporosis(OP)  is an age-related bone disease that has emerged as a worldwide public health concern due to its increasing incidence and high disability rate. The Tanshinol (D (+) β-3,4-dihydroxyphenyl lactic, TS), a water-soluble ingredient extracted form Salvia miltiorrhiza, has been proved effective in attenuating OP conditions both in vivo and vitro studies. However, its clinical application is limited by scattered evidence. Purpose: This meta-analysis aims to integrate OP animal model studies to systematically illustrate the antiosteoporosis effects of TS. Methods: Electronic searches of related studies were conducted in the following databases: EMBASE, PubMed, Web of Science, Cochrane Library, Chinese National Knowledge Infrastructure, Chinese VIP Database, Chinese Biomedical Literature Database, and Wanfang. The retrieval date was January 2022 and no time as well as language restrictions were applied. The risk of potential bias was tested by the CAMARADES 10-item quality checklist for each study and modifications were performed as appropriate. The primary outcome was bone mineral density (BMD, including femur and lumbar); and secondary outcomes were parameters for trabecular bone: bone volume over total volume(BV/TV), trabecular number(Tb.N), trabecular thickness(Tb.Th), trabecular separation (Tb.Sp) and conditions of the femur including bone maximum load and bone elastic load. Results: 9 studies including 168 rats were enrolled in this analysis. The Egger’s test indicated that publication bias was exited among different studies regarding the primary outcome. This systematic review indicated that the TS significantly increased the BMD-femur(SMD=4.40; 95%CI=1.61 to 7.19; P=0.002, I2=94.6%), BMD-lumbar (SMD=6.390; 95%CI=2.036 to 10.744; P=0.004, I2=95.9%), BV/TV(SMD=0.790; 95%CI=0.376 to 1.204; P=0.000, I2=10.8), Tb.N(SMD=0.690; 95%CI=0.309 to 1.071; P=0.000, I2=12%), Tb.Th(SMD=0.772; 95%CI=0.410 to 1.134; P=0.000, I2=32.2%), and S-OCN(SMD=3.13; 95%CI=0.617 to 5.65; P=0.015, I2=92.3%), while Tb.Sp level was remarkably decreased in OP models compared to controls (SMD=-0.822; 95%CI= -1.207 to -0.437; P=0.000, I2=0%). Moreover, treatment of the TS was associated with a significant improvement of the bone biomechanical indicators including bone maximum load(SMD=0.912; 95%CI=0.370 to 1.455; P=0.001, I2=40%) and elasticity load (SMD=0.821; 95%CI=0.290 to 1.351; P=0.002, I2=0%). Conclusion: Our study indicated that the TS could promote BMD, bone micro-architecture, bone biomechanics and S-OCN expression in rats and might shed light upon further clinical applications.